Hubungan Kelompok Umur dan Peran Suami dengan Tingkat Depresi pada ibu Postpartum - Yesi Putri; Dilfera Hermiyati; Rafika Ramlis (Journal Of Midwifery And Nursing Studies, 2021)
Depression is a mood disorder which is characterized by deep and continuous moodiness and sadness so that the enthusiasm for life is lost, there is no disturbance in assessing reality (Reality Testing Ability), the personality remains intact (splitting of personality) behavior can be disturbed but within limits. normal limit. Post partum is the separation of the placenta from the uterine wall, so the mother will experience changes according to the amount of hormones, so the mother needs time to adjust. The purpose of this study was to determine the factors associated with the level of depression in post partum patients at BPM Jumita, SST, M.Kes. This type of research is an Analytical Survey with a Cross Cestional Syudy research design and a test design using the Chi Square test with a maximum error value of a 0.05. The sample consisted of 25 respondents who were taken from mothers during the Post Partum period. Sampling method using Total Sampling. Sources of data in this study using primary data derived from interviews using questionnaires and for measuring depression in postpartum mothers using the EPDS questionnaire (Edenburgh Postpartum Depression Scale) with the provision that if the stress level of postpartum mothers is mild depression is 2-7, the stress level is moderate depression. 8-10, depression stress level Major depression >10. The results of data analysis showed that there was a relationship between the age group and the level of depression in postpartum mothers with p value = 0.001. There is a relationship between the role of the husband and the level of depression in post partum patients with p value = 0.000.